Impact of Intrauterine Insults on Fetal and Postnatal Cerebellar Development in Humans and Rodents - Judith A. W. Westerhuis; Jeroen Dudink; Bente E. C. A. Wijnands; Chris I. De Zeeuw; Cathrin B. Canto (Cells)
Many children suffer from neurodevelopmental aberrations that have long-term effects. To understand the consequences of pathological processes during particular periods in neurodevelopment, one has to understand the differences in the developmental timelines of brain regions. The cerebellum is one of the first brain structures to differentiate during development but one of the last to achieve maturity. This relatively long period of development underscores its vulnerability to detrimental environmental exposures throughout gestation. Moreover, as postnatal functionality of the cerebellum is multifaceted, enveloping sensorimotor, cognitive, and emotional domains, prenatal disruptions in cerebellar development can result in a large variety of neurological and mental health disorders. Here, we review major intrauterine insults that affect cerebellar development in both humans and rodents, ranging from abuse of toxic chemical agents, such as alcohol, nicotine, cannabis, and opioids, to stress, malnutrition, and infections. Understanding these pathological mechanisms in the context of the different stages of cerebellar development in humans and rodents can help us to identify critical and vulnerable periods and thereby prevent the risk of associated prenatal and early postnatal damage that can lead to lifelong neurological and cognitive disabilities. The aim of the review is to raise awareness and to provide information for obstetricians and other healthcare professionals to eventually design strategies for preventing or rescuing related neurodevelopmental disorders.